Analysis of non uniform surface current distribution on thick and thin wire antenna - Abd. Rahman, Rais Rabani (2013)
When wires are closely parallel, the surface current distribution becomes non uniform. Normal mode helical antenna is choosing in particular in order to study the effect of surface current distribution along its segmentation from the excitation segments towards the end of the antenna length. Antenna of different wire geometries such as wire thickness, and number of turn is designed to analyze anticipated results. The frequency operating in UHF band frequency spectrum is choose as a contribution towards widely application nowadays. The surface current distribution of thin wire antenna is not uniform as well for thick wire antennas. The difference is that thicker wire antennas results higher amount of current comparing to thin wire antennas. Higher amount of current of the surface wire antenna produce better gain and higher magnetic field strength value.